RETRACTED: Energy and mass transport through hybrid nanofluid flow passing over an extended cylinder with the magnetic dipole using a computational approach - Khan, M. Riaz; Ahammad, N. Ameer; Alhazmi, Sharifah E.; Ali, Aatif; Abdelmohimen, Mostafa A. H.; Allogmany, Reem; Tag-Eldin, Elsayed; Yassen, Mansour F. (Frontiers in Energy Research, 2022)
The objective of this research is to evaluate the heat and mass transfer in a water-based Darcy Forchhemier hybrid nanofluid (hnf) flow across an expanding cylinder. The fluid flow has been studied under the influence of magnetic field, viscous dissipation, heat source, thermal radiation, concentration stratification and chemical reaction. Carbon nanotubes (CNTs) and iron ferrite (Fe3O4) nanoparticles (nps) are added to the water, for the purpose to synthesized hnf. The fluid flow has been induced in the presence of gyrotactic microorganisms and the Non-Fick’s Model. Microorganisms are used, in order to stabilize scattered nanoparticles through hybrid nanofluid. The phenomena have been modeled in the form of nonlinear system of PDEs. The modeled equations are reduced to dimensionless system of ODEs through using similarity substitution. The numerical solution of the derived sets of nonlinear differential equations is obtained through using Parametric Continuation Method. The impact of physical constraints on temperature, velocity, concentration and microorganism profiles are presented through Figures and Tables. It has been observed that the heat and mass transport rate increase with the rising effect of curvature parameter, while declines with the effect of thermal stratification parameter.